Natural Antioxidants and Aquatic Animal Health - Jia, Rui (Antioxidants, 2025)
In intensive aquaculture, aquatic animals inevitably encounter multiple stressors due to environmental fluctuations, triggering various stress responses, with oxidative stress being the most prevalent [...]